ЕСТЕТ ИЧНИЙ АНАЛІ З МУЗИЧНОГО ТВОРУ ЯК ЗАСІБ ІНТЕГР АЦІЇ МИСТЕЦ ЬКИХ ДИСЦИПЛІ Н - Tkach, M (Continuing Professional Education: Theory and Practice, 2019)
Тhe article highlights the essence of aesthetic analysis of musical works as a means of integrating arts disciplines. The results of laboratory experiment in artistic higher education institutions to identify ways of personal significance of artistic synthesis.